Plagiarism among Undergraduate Students in an Engineering- Based University: An Exploratory Analysis - Wan, Roselind (EuroJournals Publishing Inc., 2011)
Plagiarism is a complex phenomenon and addressing the problem requires a thorough examination of various constructions underpinning it occurrences. This paper explores plagiarism practices and its contributing factors among the engineering undergraduates in a higher learning institution. 500 questionnaires, consisting of 50 items, were distributed to the Engineering students as respondents in this study. The investigation hinges on four dimensions which include awareness about plagiarism, knowledge on academic referencing, intent and extent in committing plagiarism and contributing factors towards plagiarism. The findings provide some sociological insights for better understanding of the problem among students in universities.